2011
DOI: 10.1158/0008-5472.can-11-0242
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Phenotype and AMP Kinase Modify the Pathologic Response of Tumor Xenografts to VEGF Neutralization

Abstract: VEGF antagonists are now widely used cancer therapeutics, but predictive biomarkers of response or toxicity remain unavailable. In this study, we analyzed the effects of anti-VEGF therapy on tumor metabolism and therapeutic response by using an integrated set of imaging techniques, including bioluminescence metabolic imaging, 18-fluorodeoxyglucose positron emission tomography, and MRI imaging and spectroscopy. Our results revealed that anti-VEGF therapy caused a dramatic depletion of glucose and an exhaustion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 47 publications
(55 reference statements)
13
63
0
Order By: Relevance
“…Furthermore, the decrease in median tumor ADC and narrowing of the ADC histogram observed here (Fig. 5) has been observed previously after anti-VEGF treatment in both preclinical (22) and clinical (23,50) studies, in which it has been attributed to a variety of factors, including cell swelling (22), atypical necrosis, and chronic hypoxia (50), as well as decreased edema (23).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the decrease in median tumor ADC and narrowing of the ADC histogram observed here (Fig. 5) has been observed previously after anti-VEGF treatment in both preclinical (22) and clinical (23,50) studies, in which it has been attributed to a variety of factors, including cell swelling (22), atypical necrosis, and chronic hypoxia (50), as well as decreased edema (23).…”
Section: Discussionsupporting
confidence: 84%
“…The interplay between tumor vascularity and metabolism is of significant interest, as high glucose metabolism with low blood flow correlates with poorer patient outcomes (20,21). The glycolytic phenotype of tumor xenografts was recently found to play a role in the response of preclinical tumor models to anti-VEGF therapy (22). Furthermore, metabolic changes measured with proton magnetic resonance spectroscopy (MRS) in glioblastoma multiforme tumors treated with cediranib are highly predictive of 6-month overall survival (23).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that short-term anti-VEGF therapy causes severe impairment of glucose and ATP levels in tumors (14). In this study, we also found that the response to short-term VEGF blockade is strongly dependent on the glycolytic phenotype of the tumor.…”
Section: Introductionsupporting
confidence: 72%
“…Metabolic alterations in cancer cells may derive from genetic changes associated with cell transformation such as dysregulated activity of HIF1 (9), loss of p53 or altered expression of c-Myc or Akt (10), or be triggered by inhibition of mitochondrial respiration (11). Moreover, changes in tumor metabolism can also follow reduction in energy sources (O 2 , glucose, glutamine) in the tumor microenvironment associated with antiangiogenic therapy (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation